Efektivitas Model Problem Based Learning melalui Media PRAYAKU sebagai Upaya Meningkatkan Pemahaman Konsep IPAS Siswa Kelas IV SD - Desta Abella Afita Putri Rahmawati; Sekar Dwi Ardianti; Imaniar Purbasari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Understanding a concept is crucial in shaping students’ thinking, particularly in understanding the IPAS concept; therefore, innovative teaching methods are needed to encourage students’ active engagement and enhance their understanding. One such method is the application of the Problem-Based Learning (PBL) model with the aid of the PRAYAKU media. This study aims to analyze the differences in students’ pretest and posttest average scores and to assess the improvement in students’ understanding of the IPAS concept. The method used in this study was a quantitative approach employing a pre-experimental, one-group pretest-posttest design. Data collection techniques included observation, interviews, tests, and documentation. The research instruments comprised observation sheets, interview sheets, and test sheets. Data analysis techniques in this study included a normality test, a paired-sample t-test, and an N-Gain test. The results showed that the pretest average score of 52 increased to 83 on the posttest, with a significance level (two-tailed) of 0.000, which is less than 0.05. The researcher also obtained an N-Gain Score of 0.6899, which falls into the “moderate” improvement category. Based on the results of the data analysis, it can be concluded that there is a significant difference between the average pretest and posttest scores for IPAS concept understanding, and that the students’ understanding of IPAS concepts has improved.